2014
DOI: 10.4137/cmc.s11535
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary versus Intravenous Adenosine-Induced Maximal Coronary Hyperemia for Fractional Flow Reserve Measurements

Abstract: BACKGROUNDMaximal hyperemia is the critical prerequisite for fractional flow reserve (FFR) assessment. Despite intravenous (IV) adenosine currently being the recommended approach, intracoronary (IC) administration of adenosine constitutes a valuable alternative in everyday practice. However, it is surprisingly unclear which IC strategy allows the achievement of FFR values that are comparable to IV adenosine.OBJECTIVESThis study sought to compare increasing doses of IC adenosine versus IV adenosine for FFR.METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Recent studies did not find significant differences of hyperemic response between IC and intravenous administration. 23,24 As already previously mentioned, the degree of contrast-induced hyperemia depends on the biophysical properties of the contrast medium. Thus, as our study was performed with iodixanol, we cannot generalize our findings to other protocols of cFFR.…”
Section: Study Limitationsmentioning
confidence: 94%
“…Recent studies did not find significant differences of hyperemic response between IC and intravenous administration. 23,24 As already previously mentioned, the degree of contrast-induced hyperemia depends on the biophysical properties of the contrast medium. Thus, as our study was performed with iodixanol, we cannot generalize our findings to other protocols of cFFR.…”
Section: Study Limitationsmentioning
confidence: 94%
“…The lowest FFR value achieved with IC adenosine bolus varied according to the dose used. Two studies demonstrated no statistically significant difference in FFR values measured with IC adenosine at a dose of the 150 μg and IV adenosine . Other studies reported the same conclusion but with significantly lower IC adenosine dose of 40 and 80 μg in the RCA and left coronary artery, respectively .…”
Section: Resultsmentioning
confidence: 80%
“…Continuous intravenous (IV) adenosine is considered the standard method to induce maximal hyperemia, but its use in the catheterization laboratory is time‐consuming and expensive. Intracoronary (IC) bolus administration is an alternative to IV adenosine in inducing maximal hyperemia . Multiple studies have been carried out to compare the diagnostic accuracy, tolerability, and costs of IV and IC adenosine administrations in intermediate coronary lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The former is the established gold standard and is calculated during hyperaemia, originally obtained with adenosine, and averaged through several cardiac cycles. In order to facilitate FFR adoption, two different approaches have been proposed: intra coronary adenosine administration (13), and more recently introduction of contrast medium as an alternative hyperemic agent. Contrast medium induced FFR, studies have shown a good correlation between contrast induced Pd/Pa and adenosine mediated FFR (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%